The Influence of Interbank Money Market Stress Levels on Credit Markets During the Postcrisis Period in US And Euro Area - Đukić, Đorđe; Đukić, Mališa (Economic Annals, 2011)
Despite the anti-crisis measures in the US and the euro area that were the policy response to the global financial crisis in 2007 and 2008, the stress on the interbank money market was still present in 2009 and 2010. The increasing inflationary pressures will require an increase in the ECB key interest rate in the second half of 2011. The over indebted euro area countries will have to raise funds by issuing and selling bonds with high yields. Taking into account such an environment, in this paper we analyse the relevant interbank money market stress indicators during 2010 and the beginning of 2011, in order to estimate the effects of money markets interest rate movements on credit market interest rates, primarily in the euro area, during the post-crisis period.